C++ PROGRAM IMPLEMENTING THE ABELIAN GROUP ABSTRACT - Ruiz L., Edgar (2004)
This article presents a C++ Program implementing the Commutative or Abelian Group Algebraic Concept. The whole Program code that manages abelian class objects as a new data abstract type, TAD, using concepts such as operators overcharge is shown. Implementation has been carried out in a Dev C++ 4.1 compiler, a GNU compiler with GLP licence.